Analisis Hadis-hadis Terkait Garar dan Hukumnya dalam Jual Beli Juzāf - Muhammad Taufan Djafri; Abdul Rahman Sakka; La Ode Ismail Ahmad (NUKHBATUL 'ULUM: Jurnal Bidang Kajian Islam, 2022)
The purpose of this study is to analyze the sanad hadiths related to garar and the law in buying and selling juzāf. This research is a qualitative research, the type of research is library research, and uses a thematic approach. The results of the study show that the hadiths that are raised and become references for the prohibition of garar in buying and selling are considered mutually reinforcing one another, especially because they are supported by the valid hadith li żātihi in Ṣaḥīḥ Muslim. Garar in buying and selling is unclear whether or not the object exists and the shape, size, weight or volume of the object is unclear. Garar in the sale and purchase of juzāf is permissible by the majority of scholars because the garar is small with conditions set by the scholars.